The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/aen.12397
|View full text |Cite
|
Sign up to set email alerts
|

Sharpshooters: a review of what moves Xylella fastidiosa

Abstract: Sharpshooters (Hemiptera: Cicadellidae: Cicadellinae) and spittlebugs (Hemiptera: Aphrophoridae: Aphrophorinae) have a worldwide distribution and are often associated with many crops. Because the geographic range of sharpshooters and spittlebugs often overlaps with the range of the plant pathogenic bacterium Xylella fastidiosa, the importance of these groups of insects in spreading X. fastidiosa rises to the level of a major socioeconomic problem. Managing diseases caused by X. fastidiosa is challenging for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 250 publications
0
41
0
Order By: Relevance
“…Nevertheless, all the progress made in the understanding of the traits that contribute to vector acquisition and transmission in X . fastidiosa , reported in several reviews (Redak et al ., 2004; Chatterjee et al ., 2008; Krugner et al ., 2019), will be helpful to interpret and inform our findings in the context of X . fastidiosa detection and spread in Europe.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, all the progress made in the understanding of the traits that contribute to vector acquisition and transmission in X . fastidiosa , reported in several reviews (Redak et al ., 2004; Chatterjee et al ., 2008; Krugner et al ., 2019), will be helpful to interpret and inform our findings in the context of X . fastidiosa detection and spread in Europe.…”
Section: Introductionmentioning
confidence: 94%
“…In the Americas, the role of X . fastidiosa 's vectors, such as sharpshooters and spittlebugs, in the epidemiology and spread of the disease has been widely studied and reviewed (Redak et al ., 2004; Chatterjee et al ., 2008; Krugner et al ., 2019). Recently in Europe, transmission testing has revealed that the spittlebugs Philaenus spumarius , Philaenus italosignus , and Neophilaenus campestris are efficient vectors in the Apulia region, Italy (Cornara et al ., 2017; Cavalieri et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-negative xylem-limited non-circulative propagative gamma-proteobacterium Xylella fastidiosa was ranked as the more serious of the two insect-transmitted bacterial pathogens [4]. This system was reviewed recently [12,87,88,89,90]. Reproduction in the vector takes place on the cuticular surface of the anterior foregut [91].…”
Section: Other Bacterial Pathosystemsmentioning
confidence: 99%
“…Xylella fastidiosa is a gram-negative bacterium and the causal agent of Pierce's disease in grapevines, as well as numerous other leaf scorch diseases [1]. Restricted to the xylem tissue of plants, X. fastidiosa is transmitted to grapevine by xylem-feeding insects, including sharpshooters, leafhoppers, and spittlebugs [2,3]. The transition between colonization of the insect vector and plant host is a highly regulated process, which relies on quorum sensing to transition between an adhesive biofilm state and systemic motility dependent on type IV pili [4,5].…”
Section: Introductionmentioning
confidence: 99%